1995
DOI: 10.1897/1552-8618(1995)14[861:doteff]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Development of Toxic Equivalency Factors for PCB Congeners and the Assessment of TCDD and PCB Mixtures in Rainbow Trout

Abstract: This study was undertaken to evaluate the relationship between mammalian and piscine 2,3,7,8-tetrachlorodibenzop-dioxin (TCDD) toxic equivalency factors (TEFs) for PCBs, based on induction of CYPlA enzyme activity, catalytic protein, and mRNA. Rainbow trout administered a single i.p. injection of TCDD had an average (+sD) ED50 of 0.91 t 0.14 pg TCDD/kg for induction of ethoxyresorufin 0-deethylase (EROD) activity. Ortho-substituted PCB congeners 2,3,3',4,4'-pentachlorobiphenyl (PCB 105), 2,3',4,4',5-pentachlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 17 publications
6
31
0
Order By: Relevance
“…In this study ( Fig. 4, Table 2) as in several others [15,[46][47][48], EROD was found to be more sensitive than CYP1A protein as an index of induction. Moreover, EROD activity can be measured easily and rapidly.…”
Section: Measurement Of Cyp1a Proteinsupporting
confidence: 75%
See 3 more Smart Citations
“…In this study ( Fig. 4, Table 2) as in several others [15,[46][47][48], EROD was found to be more sensitive than CYP1A protein as an index of induction. Moreover, EROD activity can be measured easily and rapidly.…”
Section: Measurement Of Cyp1a Proteinsupporting
confidence: 75%
“…Chem. 15,1996 M.E. Hahn et al The PLHC-1 cells were treated with the indicated inducers, and EROD and CYP1A were measured as described in the legends to Figures 4 and 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is likely that higher doses of 3,4,5-HCB would have been required to demonstrate antiestrogenic effects in trout. Our results are consistent with the work of Monosson et al [22,23], who reported that similar doses of 3,4-TCB (a congener with a CYP1A induction po-tential comparable to that of 3,4,5-HCB [38]) did not suppress Vg synthesis in sexually mature striped bass and white perch.…”
Section: Discussionsupporting
confidence: 93%